Positive mass budgets of high-altitude and debris-covered fragmented tributary glaciers in Gangotri Glacier System, Himalaya - Hussain, Md. Arif; Azam, Mohd. Farooq; Srivastava, Smriti; Vinze, Parul (Frontiers in Earth Science, 2022)
Glacier-wide mass balances (MBs) of the Gangotri, Chaturangi, Raktavaran, Meru, and Gangotri Glacier System are reconstructed with a temperature-index (T-index) model using bias-corrected ERA5 data at a daily temporal resolution over 1979-2020. The model output is calibrated against available geodetic MB for Gangotri Glacier System and validated with satellite-derived snow line altitudes (SLAs) for Gangotri Glacier. Gangotri and Meru glaci-ers show mean mass wastage of –0.88 ± 0.31 m w.e. a‒ˡ (meter water equivalent per year) and ‒0.17 ± 0.29 m w.e. a‒ˡ, respectively whereas the mass budgets of fragmented Cha-turangi and Raktavaran glaciers are positive with the mean values of 0.49 ± 0.17 m w.e. a‒ˡ and 0.62 ± 0.15 m w.e. a‒ˡ, respectively over 1979-2020. Gangotri Glacier’s tongue is cov-ered by thick debris having several supra-glacial lakes and ice cliffs (considered as melting hotspots); therefore, despite the presence of thick debris, we assume the melting over this area as of clean glacier. The whole Gangotri Glacier System shows a moderate wastage of ‒0.27 ± 0.25 m w.e. a‒ˡ. The positive MBs of the Raktavaran and Chaturangi glaciers are due to their high area-elevation distribution and heavily debris-covered tongues. The positive MBs on these fragmented glaciers are due to non-climatic topographic reasons and should not be misunderstood as climate change deniers or compared with Karakoram Anomaly. Modelled MBs are most sensitive to the threshold temperature for melt. The altitudinal MB sensitivities to all model parameters become negligible above 6200 m a.s.l.